Strategi Pengembangan Ekonomi Pedesaan Melalui Penguatan Potensi Sumberdaya - Vanya Benita; Nisa Anggilia; Qonitah Berliana; Regyna Renata (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
Abstract. Village development had a significant tendency to be handled uniformly by the central government throughout the New Order era. Village development programs are more top-down in nature. Village development was increasingly delegated to the community itself throughout the reform era. Central and local governments take on facilitator positions and functions, offering financial support, mentoring and supervision. Many initiatives to reduce poverty have been undertaken, including the Assistance Program for Disadvantaged Communities and Education for Presidents of Disadvantaged Villages. Village development programs are more bottom-up or a mixture of bottom-up and top-down. This research is included in qualitative research, namely research that does not use mathematical calculations, statistics and so on, but uses scientific emphasis or findings that cannot be achieved using statistical procedures or other methods of quantification. In spurring economic growth, economic policy must embrace a new paradigm where people's economic empowerment must be the main concern. Because most people in rural areas live in the agricultural sector and this sector still makes a large contribution to the regional economy, empowering the people's economy also means building a better rural economy. Industrial development must pay attention to backward linkages with the agricultural sector or primary sector, while forward linkages must pay attention to processing to increase added value and good marketing so that the products produced are not wasted.